Temporal variation of extreme precipitation events in Lithuania - Egidijus Rimkus; Justas Kažys; Arūnas Bukantis; Aleksandras Krotovas (Oceanologia, 2011)
Heavy precipitation events in Lithuania for the period 1961-2008 were analysed. The spatial distribution and dynamics of precipitation extremes were investigated. Positive tendencies and in some cases statistically significant trends were determined for the whole of Lithuania. Atmospheric circulation processes were derived using Hess & Brezowski's classification of macrocirculation forms. More than one third of heavy precipitation events (37%) were observed when the atmospheric circulation was zonal. The location of the central part of a cyclone (WZ weather condition subtype) over Lithuania is the most common synoptic situation (27%) during heavy precipitation events. Climatic projections according to outputs of the CCLM model are also presented in this research. The analysis shows that the recurrence of heavy precipitation events in the 21st century will increase significantly (by up to 22%) in Lithuania.